Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
please be more detailed while posting questions.
the variables are just variables, they don't mean anything...
To be More Specific:
f(x) = 2x + 3
f(1) = 2+3
f(a) = 2a + 3
You haven't given us any info to say not to.. So my assumption is that p(a)=0.05a is the function way of writing p=0.05a. Therefore you can substitute that into t(p) to get \[t(a)=3(0.05a)=0.15a\]
@stardust3829 DId u get my point
but @Yahoo! also has a point. Because of the lack of information this can be interpreted in different ways.
not really, a little bit, but not much :) sorry
how does knowing what the functions are saying, help to know how to combine them?
You've given us two functions and you want us to find a third function which returns the same variable as one of the functions but takes a different input. <<<--- confusing sentence.
y=2x is the same as y(x)=2x. x being your input and y your output.
now if you had say h=5y. that's the same as saying h(y)=5y... with y as your input and h your output.
Now you want to find h(x). which has an input of x but an output of y. so from that you know you nee to combine the equations.
you get h(y)=h(2x) and since your h=5y.. y the input. you get h(2x)=5(2x).
but you want it as h(x). so you simplify the right side 5(2x)=10x.. and now your h=10x, which is the same as h(x)=10x